Evaluación de la acción coagulante de la semilla de durazno y tallo de nopal: aclaración de aguas turbias - Chávez Herrera, Santiago Alberto (2018)
The use of water resources in recent years has become an essential resource both for human consumption and for global productive activities.The excessive use for various purposes, has allowed the water to pass through several processes and costly treatments for their recovery in the same or better conditions, from where they were taken.For this reason, we will focus on the water resource used for recreational activities, such as spas, where the problem focuses on the turbidity that is produced by the constant use by bathers, the presence of suspended solids in the water, delay time to achieve complete sedimentation, therefore, it is necessary to use chemical coagulants / flocculants for this process, the chemical compound most demanded by these recreational activities is aluminum sulfate, at the same time its excessive demand has caused the destruction of large areas for obtaining the raw material that is, aluminum, for this reason we present an environmental, sustainable alternative, such as the use of Nopal, which has proven coagulant properties in the laboratory, these coagulant properties are attributed to its mucilage , an organic substance with a viscous texture.Next, we will present the design of a system for the use of cactus in the pool, which will allow us to obtain effective results when giving the maintenance of the pools, in this way we protect and take care of the water resources, ensuring the sustainability of the others means. To sediment the suspended particles and decomposing organic matter present in natural waters it is necessary to apply coagulants that allow the agglomeration of solids and improve the quality of the water. Chemical coagulants such as aluminum sulfate, aluminum poly chloride or ferric chloride, cause neurodegenerative diseases to humans. It is convenient to use natural products in the treatment of water, which allow to efficiently remove the turbidity and color, without causing side effects to health. Replacing the traditional coagulant with a natural one is one of the alternatives to contribute to the protection of the environment and in this way minimize the impacts produced by the excessive use of chemical compounds.The use of these coagulants represents an important advance in sustainable environmental technology, since they are renewable resources and their application is directly related to improving the quality of life of underdeveloped communities. With the implementation of the nopal use system, we will be saving the owner time and money, because this system is specially designed for the reutilization of the cactus stem. As it was previously named, this design will have 2 lanes which will facilitate the use of this system and will allow the owner or the person in charge of the pool to obtain better results in sedimentation than by applying aluminum sulphate.Once the knowledge about the maintenance of water from pools with nopal is expanded, we will be influencing and promoting the use of natural and sustainable coagulants, which in turn does not entail environmental problems in its use or application, such as aluminum sulphate.